Edukasi Masyarakat dalam Menerapkan 3T dalam Upaya Mempersiapkan Bali Bangkit - Kadek Prasilia Candra Dewi; Adie Wahyudi Oktavia Gama; Dewa Ayu Putu Adhiya Garini Putri (IKIP PGRI Bojonegoro, 2022)
Bali is Indonesia's gem for its truly beautiful island. It is one of the world's most favorite tourist destinations. However, the COVID-19 virus outbreak has been making huge impacts worldwide socially and economically, since the beginning of 2020. The impacts and result can be seen as follow: social distancing, work from home, also stay at home. Roughly speaking, people must not travel anywhere during this pandemic. Strict rules applied for working, especially having a vacation. It definitely hits Bali's economy to reach its low graphic level. Besides that, the health of the people in Bali is threatened. Intensively promoting health to the community is the main point to break the chain of virus transmission. The 3M steps guide is important as early prevention, namely washing hands, maintaining distance, wearing masks). Meanwhile, 3T steps are important too, namely, Testing, Tracing, Treatment. As people have aware of the 3M, but not everyone knows 3T. These guides aimed to provide information to the Balinese people about the role of the community in handling COVID-19. In its implementation, namely conducting online counseling, 365 participants officially registered and 180 participants attended from various circles. This service is expected to be able to educate the public about 3T so that people understand and participate in controlling COVID-19 and together make Bali Bangkit a success. Bali adalah permata Indonesia untuk pulau yang benar-benar indah. Ini adalah salah satu tujuan wisata paling favorit di dunia. Namun, wabah virus COVID-19 telah memberikan dampak besar di seluruh dunia secara sosial dan ekonomi, sejak awal tahun 2020. Dampak dan hasilnya dapat dilihat sebagai berikut: social distancing, work from home, juga stay at home. Secara kasar, orang tidak boleh bepergian ke mana pun selama pandemi ini. Aturan ketat diterapkan untuk bekerja, terutama berlibur. Ini pasti memukul perekonomian Bali untuk mencapai tingkat grafis yang rendah. Selain itu, kesehatan masyarakat di Bali terancam. Mengkampanyekan kesehatan secara intensif kepada masyarakat menjadi poin utama untuk memutus mata rantai penularan virus. Panduan langkah 3M penting sebagai pencegahan dini yaitu cuci tangan, jaga jarak, pakai masker). Sedangkan langkah 3T juga penting yaitu, Testing, Tracing, Treatment. Seperti yang sudah diketahui orang tentang 3M, namun tidak semua orang mengetahui 3T. Dalam kegiatan ini bertujuan untuk memberikan informasi kepada masyarakat Bali tentang peran masyarakat dalam penanganan COVID-19. Dalam pelaksanaannya yaitu melakukan penyuluhan online, 365 peserta terdaftar dan 180 peserta hadir dari berbagai kalangan serta kenaikan pengetahuan dari masyarakat sebesar 135%. Kegiatan ini diharapkan dapat mengedukasi masyarakat tentang 3T agar masyarakat paham dan ikut serta dalam pengendalian COVID-19 dan bersama-sama mensukseskan Bali Bangkit.